Oblast po zlomu moderne resničnosti: ljudje iz vasi Makuleke v Južni Afriki - Urh, Jana (Teorija in praksa, 2000)
In the following pages power is no longer connected with classical political field only, but is dispersed to all domains of social life, recognized through special events and put into the field of secret knowledge. Anthropological field-notes from Makuleke, Mabilique and Makahlule villages in the Northern Province of the Republic of South Africa are translated as a text. Power is always connected with specific perception of reality: in Makuleke it is bind to a mysterious behavior of a chief, connected with perception of an initiation school as a secret society and with secret knowledge/practice of traditional healers. Article ends and starts again with a question of initiation of anthropologists into the domain after the break of modern reality, where life among people itself becomes a process of recognizing and knowing.
Keywords: Južnoafriška republika; anthropology; antropologija; authority; oblast; politics; politika; tradicionalna družba; raziskave